c-Met: A Promising Therapeutic Target in Bladder Cancer - Feng Y; Yang Z; Xu X (Cancer Management and Research, 2022)
Yanfei Feng,1,* Zitong Yang,2,* Xin Xu2 1The Second Affiliated College, Zhejiang Chinese Medical University, Hangzhou, People’s Republic of China; 2Department of Urology, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xin Xu, Department of Urology, The First Affiliated Hospital, Zhejiang University School of Medicine, 79th Qingchun Road, Hangzhou, 310003, People’s Republic of China, Tel +86 19858164566, Fax +86 571 87236114, Email drxuxin@zju.edu.cnAbstract: Mesenchymal-epithelial transition factor (c-Met) belongs to the tyrosine kinase receptor family and is overexpressed in various human cancers. Its ligand is hepatocyte growth factor (HGF), and the HGF/c-Met signaling pathway is involved in a wide range of cellular processes, including cell proliferation, migration, and metastasis. Emerging studies have indicated that c-Met expression is strongly associated with bladder cancer (BCa) development and prognosis. Therefore, c-Met is a potential therapeutic target for BCa treatment. Recently, the aberrant expression of noncoding RNAs was found to play a significant role in tumour progression. There is a close connection between c-Met and noncoding RNA. Herein, we summarized the biological function and prognostic value of c-Met in BCa, as well as its potential role as a drug target. The relation of c-Met and ncRNA was also described in the paper.Keywords: c-Met, HGF, noncoding RNA, bladder cancer, review